Expolation Of The Relationship Between Live Host And Audience On Shopee Live - Nurhayati, Lina; Widodo, Arry; Rubiyanti, R. Nurafni (International Journal Labs, 2025)
This study aims to explore the influence of Interactional Element and Audience Characteristic on Purchase Intention within the context of Shopee Live, while also examining the mediating roles of Perceived Influencer and Consumer attitude. A quantitative approach was employed through a survey conducted among active Shopee Live users in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings indicate that Interactional Element has a positive and significant effect on both Perceived Influencer and Purchase Intention. Audience Characteristic significantly influences both Consumer Attitude and Purchase Intention. Additionally, both Perceived Influencer and Consumer Attitude have positive effects on Purchase Intention. Mediation analysis confirms that Perceived Influencer and Consumer Attitude mediate the relationship between Interactional Element and Audience Characteristic with Purchase Intention, respectively. This study contributes theoretically to the understanding of digital interaction and audience alignment in shaping consumer behavior in live commerce. Practically, the results offer insights for developing more interactive and personalized digital marketing strategies for e-commerce businesses.